Accessibility of Public Services for Persons with Disabilities at the Makassar City Social Service - Herlina Sakawati; Andi Ceri Susilawati; Sulmiah Sulmiah (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
Persons with disabilities have the same rights as the society in general to get access to public services. To facilitate services for persons with disabilities, the government needs to maximize the accessibility of existing public services. In this study, an analysis was carried out on the accessibility of public services for service users with disabilities at the Makassar City Social Service, using the qualitative method. Research data were obtained from observations, interviews, and analysis of documents related to the accessibility of disability services. According to the research results obtained in the field, it is known that the accessibility possessed by the Makassar City Social Service does not reflect the existence of safety, comfort, convenience, and aesthetics in providing services to persons with disabilities. The physical facilities used in providing services to persons with disabilities are equated with the facilities used by ordinary people who do not have deficiencies.